PENGARUH MINUMAN KERAS TERHADAP MENINGKATNYA ANGKA KECELAKAAN LALU LINTAS DI KABUPATEN SORONG DIMANA BERTENTANGAN DENGAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 - Batkormbawa, Heber Yohanes; Baho, Dayen; R. Morintoh, Raymond (Ensiklopedia of Journal, 2024)
Miras or alcoholic beverages have various levels and types but have the same impact on those who consume them, namely gradually losing a person's consciousness in a certain time. In this study, the author tries to describe the impact of someone consuming excessive alcohol so that it causes a traffic accident which is entirely the negligence of the individual who has consumed alcohol or alcoholic beverages and is one of several factors in the occurrence of traffic accidents. The problem studied in this study is how alcohol or alcoholic beverages greatly affect the increasing number of traffic accidents which can cause victims to suffer serious injuries or minor injuries resulting in other people dying, minor injuries and vehicle damage besides that alcohol can damage the younger generations of the Indonesian nation because currently the liquor trade is very uncontrolled and can be purchased by all groups. Excessive consumption of alcoholic beverages not only has an impact on the individual who consumes it but also has an impact on others and is often detrimental to others. The level of accidents caused by alcoholic beverages has occurred throughout Indonesia and is even one of the biggest reasons why traffic accidents often occur, so in this writing the author tries to create a written work that can be a benchmark for how the influence of alcoholic beverages has a major impact so that traffic accidents often occur. In the author using a normative research method and a study of Law Number 22 of 2009 as secondary data, meaning that the normative research method is a way to obtain data from library materials taken from legal articles. That the influence of alcoholic beverages on the increasing number of traffic accidents is not something that can be ignored so that it needs to be a concern for the government and society.Keywords: Traffic Accidents, Alcoholic Beverages, Sorong Regency Police